Effect of Amphipathic HIV Fusion Inhibitor Peptides on POPC and POPC/Cholesterol Membrane Properties: A Molecular Simulation Study - Martins do Canto, Antonio Manuel Teixeira (2013)
T-20 and T-1249 fusion inhibitor peptides were shown to interact with 1-palmitoyl-2-oleyl-phosphatidylcholine (POPC) (liquid disordered, ld) and POPC/cholesterol (1:1) (POPC/Chol) (liquid ordered, lo) bilayers, and they do so to different extents. Although they both possess a tryptophan-rich domain (TRD), T-20 lacks a pocket binding domain (PBD), which is present in T-1249. It has been postulated that the PBD domain enhances FI interaction with HIV gp41 protein and with model membranes. Interaction of these fusion inhibitor peptides with both the cell membrane and the viral envelope membrane is important for function, i.e., inhibition of the fusion process. We address this problem with a molecular dynamics approach focusing on lipid properties, trying to ascertain the consequences and the differences in the interaction of T-20 and T-1249 with ld and lo model membranes. T-20 and T-1249 interactions with model membranes are shown to have measurable and different effects on bilayer structural and dynamical parameters. T-1249’s adsorption to the membrane surface has generally a stronger influence in the measured parameters. The presence of both binding domains in T-1249 appears to be paramount to its stronger interaction, and is shown to have a definite importance in membrane properties upon peptide adsorption.